Distribution and tidal variation of palaemonid shrimps (Decapoda: Caridea: Palaemonidae) in artificial and natural habitats. Issue 3 (1st March 2018) - Moritzen, Laura C; Roy, Michael; Smalley, Gabriela W; Blakeslee, April M H
Abstract: Shoreline development can alter natural habitats, create novel habitats, and affect coastal community structure. Our study compares abundances and tidal variation patterns of palaemonid shrimps in artificial and natural estuarine habitats of Long Island, NY, USA. We sampled shrimps at three habitat types: floating docks, bulkheads, and natural shorelines, at high and low tides. Several possible predictor variables were explored to explain shrimp abundances across habitat types and tides, including wave action, vegetation cover, local taxonomic richness, temperature, and salinity. Shrimp abundances were mainly influenced by habitat type, temperature, taxonomic richness, and vegetation cover. Shrimp abundances were higher in artificial in contrast to natural habitats (particularly along bulkheading), higher in areas with intermediate levels of taxonomic richness, and higher in habitats with vegetation cover compared to areas without. Shrimp abundance also had a weak, but positive, correlation with temperature. Along bulkheads and in natural habitats, abundances were higher at low versus high tide; however, there was no tidal variation along floating docks. These results demonstrate how artificial structures within the intertidal zone, along with associated fouling organisms, may enhance populations of palaemonids, which are a critical component of coastal and estuarine ecosystems.